Perimenopausal Symptomatology and Menopause-Related Quality of Life [2M]. (May 2017) - Dye, Timothy; Demment, Margaret; Hyrien, Ollivier; Weber, Miriam; Morley, Christopher; Woods, James
Abstract : INTRODUCTION: Increasing evidence demonstrates a gap between women's own experience of menopause and practitioners' diagnosis and treatment of menopause-related symptoms (MRS). This study aims to identify subjective symptoms in perimenopausal women and their association with menopause-related Quality of Life (MQOL). METHODS: Women aged 45-64 enrolled in Family Medicine- and OBGYN-based primary care settings were approached electronically to participate. Women were excluded if they had past surgical history of oophorectomy, history of breast, or endometrial cancer, or were currently pregnant. In total, 70 women completed the baseline survey which included the Greene Climacteric Scale (measuring MRS) and the Utian Quality of Life Scale (measuring MQOL). Forward stepwise linear regression analyses were used to identify MRS predictors associated with MQOL scores. RESULTS: Several MQOL domains were significantly associated with MRS. Psychological symptoms were significantly associated with occupational (-0.66; p < .0001), emotional (-0.48; p < .0001), and overall quality of life (-1.71; p < .0001) MQOL scores. Depression symptoms were strongly associated with menopause health MQOL (-0.95; p < .0001), and vasomotor symptoms were strongly associated with sexual MQOL (-0.40; p 0.036). CONCLUSION: Symptomatology significantly correlates with quality of life among women of menopausal age. As psychological and depression symptoms worsen, women report diminished quality of life. Similarly, as vasomotor symptoms increase, sexual quality of life worsens. These symptoms are common, but are often poorly understood clinically. MRS should be addressed within the clinical setting with tools such as the American College of Obstetricians and Gynecologists' Practice Bulletin and EHR-based Best Practice Alerts (BPAs).